Ethical Dimensions of Corporate Disclosures in the Globalised Environment - Singh, Karamjeet; Kant, Kamal (Prabandhan: Indian Journal of Management, 2010)
Corporate entities establish accounting systems for generation of information which is generally of financial nature. The information so generated is directed by accounting principles, mandatory requirements, decisional needs, and the standards laid-down at national as well as the international level. A well laid out system of accounting facilitates the measurement of performance, planning and control. The financial and quantitative information generated need to be communicated to the stakeholders in an effective manner, and through appropriate medium, ensuring transparency as well as timeliness. The essence of accounting is in communication.